In Situ Unveiling of the Coupling Mechanism of Intercalation-Conversion Processes at the Nanoscale in Lithium–Ion/Lithium–Oxygen Hybrid Batteries - Jian-Xin Tian; Hao Chen; Zhen-Zhen Shen; Yao-Zu Zhang; Xu-Sheng Zhang; Yuan Li; Yong-Xin Cheng; Si-Jie Guo; An-Min Cao; Yu-Guo Guo; Gang Huang; Rui Wen (Journal of the American Chemical Society, 2026)
Abstract With the rapid growth in energy demand, designing a novel hybrid battery system has become increasingly important. It is critical to reveal the coupling mechanisms of intercalation-conversion hybrid cathodes and provide an in-depth understanding of structure-performance relationships for the electrochemical energy storage devices with high energy density. In this study, a hybrid cathode that combines intercalation-type LiNixCoyMn1-x-yO2 (NCM) with conversion-type oxygen (O2) is proposed. Using in situ electrochemical atomic force microscopy (EC-AFM), we elucidate that the overlithiation of the NCM cathode enhances electronic conductivity and exposes abundant active sites during discharge, thereby inducing the formation of Li2O2. Electrochemical tests demonstrate that the contributions of intercalation and conversion reactions to capacity are rate-dependent, with lower rates favoring the intercalation-dominated electrochemical process. Further scanning transmission electron microscopy characterization indicates that, during prolonged cycling, oxygen vacancies in the NCM intercalation-type cathode serve as preferential sites for the conversion-type Li–O2 intermediates, significantly enhancing the cycling stability of the battery. Ultimately, by optimizing the mass ratio between the intercalation and conversion cathodes, an enhanced cycle stability is achieved. This study offers valuable insights into modulating battery performance through multimechanism reactions in hybrid battery systems.